(untitled) - Dick, Steven J. (New York, 2003)
This volume is, first and foremost, a story of the relations between space, time and navigation, from the rise of the chronometer in the U.S. to the Global Positioning System of satellites, for which the Naval Observatory provides the time to a billionth of a second per day. It is a story of the history of technology, in the form of telescopes, lenses, detectors, calculators, clocks and computers over 170 years. It describes how one scientific institution under government and military patronage has contributed, through all the vagaries of history, to almost two centuries of unparalleled progress in astronomy.
Keywords: Astronomy,Thiên văn học; History; United States